Analisis Konstanta Euler-Mascheroni yang Diperumum pada Deret Harmonik - Rahman, Raisha Inayah; Rahman, Hairur; Herawati, Erna (Jurnal Riset Mahasiswa Matematika, 2023)
The generalized Euler-Mascheroni constant analyzes functions or sequences with specific parameters in various scientific fields. As scientific knowledge advances, the generalized Euler-Mascheroni constant continues to undergo renewal. One example is found in "On Generalized Euler-Mascheroni Constants" by G. Abe-I-Kpeng, M.M. Iddirisu, and K. Nantomah in 2022. The purpose of this study is to analyze the relationship between the generalized Euler-Mascheroni constant and harmonic series, as well as to examine its connection with signed count permutations. The analysis involves decomposing the Riemann Zeta function and using Stirling numbers of the first kind. The methodology employed in this study was literature research. This study yields new theorems concerning the generalized Euler-Mascheroni constant.